The Effectiveness Of Online Based Physics Learning In The Covid-19 Pandemic Period On The Material Of Work And Energy - Kharisma Titian Haqiqi; Eko Hariyono; Nurita Apridiana Lestari (University of Bengkulu, 2021)
The Covid-19 pandemic that hit Indonesia impacts the field of education. The learning process is usually carried out face-to-face has turned into online learning. This study aims to see the effectiveness of online learning based on the learning process, the achievement of learning objectives, and the obstacles experienced by students and teachers when doing online learning at SMA Negeri 2 Ponorogo during the Covid-19 pandemic. The quantitative descriptive method was used in this research. The online survey was used by using a questionnaire instrument through Google Form and cognitive tests. The results showed that online learning during the Covid-19 pandemic often used the WhatsApp platform and school e-learning websites. Respondents were interested in taking physics lessons during the pandemic online because respondents used many learnings. Based on the cognitive test results, the mean value of the respondents was <60 and did not meet the graduation criteria. The result shows that the respondents do not understand the materialof work and energy.. The obstacles experienced by respondents were difficulty understanding the material and questions in the form of statements on work and energy materials and limited quotas and internet networks. Based on the questionnaire, it was found that the effectiveness of online learning was 57%. It can be concluded that online-based physics learning during the Covid-19 pandemic at SMA Negeri 2 Ponorogo on adequate energy and business materials was carried out as a substitute for face-to-face learning.